The Efficacy of tele physiotherapy and comparison with routine physiotherapy treatment for patients underwent modified radical mastectomy - Kalpesh G. Vasani; Dr. V. P. Hathila; Arushi N. Bumtariya (The Bioscan, 2024)
Breast Cancer is a leading cause of women death in India and it is measured to have one out of every 28 Indian women are under risk of developing breast cancer. And as a part of treatment, Modified Radical Mastectomy can be considered as a best treatment procedure. But that to have some complications like Decreased Shoulder ROM, Pain & Disabilities. To overcome these complications we can have conventional physiotherapy protocol. But In India it is tough to have a physiotherapist in every rural area. So, this study is mainly focuses on the tele physiotherapy protocol and helps us to find out weather tele physiotherapy is helpful or not and if it is helpful, than comparison with the routine physiotherapy. So, after having this research study we have found out that the tele physiotherapy is helpful for reducing the complications like pain, ROM & Disabilities but it is not as much beneficial as routine physiotherapy. So, for the patients who resides in rural area where physiotherapy facilities are not available, those patients can be benefited by having tele physiotherapy than compared to No Physiotherapy at all.